Evaluation of Pulasan (Nephelium ramboutan-ake) Genetic Diversity in Bogor, West Java, Using Microsatellite Markers - Amelia Luisyane Puhili; Tatik Chikmawati; Nina Ratna Djuita (Journal of Tropical Life Science, 2016)
Pulasan (Nephelium ramboutan-ake (Labill.) Leenh) fruit is highly similar to rambutan rapiah (Nephelium lappaceum) fruit with ovate shape, sweet and sour fresh taste, but it has a thick rind. The diversity of pulasan is little informed including in Bogor. The objective of this study was to analyze the genetic diversity of pulasan from Bogor revealed by microsatellite marker. The DNA of 63 individuals from 10 populations of pulasan were extracted using CTAB method and amplified using two primer sets, LMLY6 (GA)9(CA)2(GA)4 dan LMLY12 (CT)11. DNA amplification product was visualized and arranged in a matrix of binary data then analyzed the value of the number of different alleles (Na), the number of effective alleles (Ne), Shannon information index (I), heterozygosity (He), and the percentage of polymorphism (PLP). The results of the analysis showed the highest genetic diversity was found in North Bogor (He=0.313). The genetic diversity within a population (61%) was higher than that among populations (39%). A dendrogram was constructed using the Unweighted Pair Group Method with arithmetic Mean (UPGMA). The similarity index ranged from 52 to 100% that means there are close relationships among individuals. Cluster analyses grouped some individuals originated from different locations in the same group. The levels of heterozygosity within a population was determined by the history of each individual in a population.